Demographic processes in animal networks are a question of time: A comment on Shizuka and Johnson (2020)
One reason why demographic processes may not have impact on social dynamics in the same way that social instability has is because of the time frame over which they occur. Here, context might matter. For example, the death of individuals can arise from different sources: a death can be age related or can be predator induced. These two contexts are unlikely to have the same impact. Older individuals that occupy high ranks in societies, and therefore are more likely to have an important role, often drop down the hierarchy before they die (Strauss and Holekamp 2019). Thus, the impact of removing an individual from the population through age-related causes could be anticipated by the system. By contrast, predation can induce very rapid changes to the membership of social groups. Effects of predation are likely to be more representative of the results of experimental studies involving the temporary